2021
DOI: 10.3390/medicina57040317
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Changes of Hands and Legs in Early Rheumatoid Arthritis

Abstract: Background and Objectives: The aim of this study was to assess if there are structural and functional changes of hands and legs already in early rheumatoid arthritis (ERA), compared with the population-based control group. Additionally, we aimed to identify if the changes are symmetrical in hands and legs and if there are factors that are associated with these changes. The study was conducted, and, thus far, the results have been controversial. Materials and Methods: The study group consisted of 83 consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(20 citation statements)
references
References 42 publications
(29 reference statements)
0
20
0
Order By: Relevance
“…2,6 Furthermore, several studies of early RA (ERA) patients revealed that in addition to bone changes, lean mass loss and fat mass gain can be evident in the early stage of RA, although the involved factors are currently unknown. 7 Likewise, we have found in our previous work 8 that ERA patients had lower arm and leg lean mass, and higher arm fat mass. The decrease in limb lean mass in ERA was associated with the elevation of C-reactive protein (CRP), 8 indicating the effects of inflammation.…”
Section: Introductionmentioning
confidence: 56%
See 4 more Smart Citations
“…2,6 Furthermore, several studies of early RA (ERA) patients revealed that in addition to bone changes, lean mass loss and fat mass gain can be evident in the early stage of RA, although the involved factors are currently unknown. 7 Likewise, we have found in our previous work 8 that ERA patients had lower arm and leg lean mass, and higher arm fat mass. The decrease in limb lean mass in ERA was associated with the elevation of C-reactive protein (CRP), 8 indicating the effects of inflammation.…”
Section: Introductionmentioning
confidence: 56%
“…Nine patients were excluded due to missing outcome data, as well another 8 patients who did not fulfill ACR/EULAR 2012 criteria for RA on a followup visit 1 year after their first visit (n = 83) (Figure 1). 8,28 To form the control group, 350 subjects adjusted for the age and gender composition of the Estonian population in 2013 were randomly selected from a primary healthcare center practice list (total number of subjects: 1854). Cross-sectional data were assembled from September 2014 to March 2015.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations